Evaluation of the Salmonella type 3 secretion system (T3SS) as part of a protein production platform for space biology applications - Kang, Min-Kyoung; Bevington, James; Tullman-Ercek, Danielle (Frontiers in Bioengineering and Biotechnology, 2025)
As interest in space exploration and in situ resource utilization grows, the potential to leverage synthetic biology and engineered microorganisms has garnered significant attention. Microorganisms provide a robust and efficient biological chassis to demonstrate the human blueprint for advancing space biology. However, progress toward these applications is hindered by the limited access to space-like environments and a lack of knowledge about how unique environmental factors affect relevant microbial systems. To address these issues, we evaluated the Salmonella Pathogenicity Island 1 (SPI-1) type Ⅲ secretion system (T3SS) as a protein production platform for space applications. Using a NASA-designed microgravity-simulating bioreactor system, we investigated the effects of simulated microgravity on cell growth, stress response, and protein secretion via SPI-1 T3SS. Our results demonstrated increased stress responses in cells grown under simulated microgravity. However, the SPI-1 T3SS maintained its ability to secrete proteins directly into the extracellular space in a single step under simulated microgravity, simplifying downstream purification processes. These findings suggest that the SPI-1 T3SS is a viable candidate for future space biology applications.